EFISIENSI SISTEM PENYIMPANAN OBAT DI BEBERAPA PUSKESMAS DAERAH YOGYAKARTA - Rosita, Melia Eka; Fajri, M. Alif; Nilansari, Anis Febri (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2024)
Medicine storage is an activity to ensure that the medicines received are placed in a place that is considered safe, which includes 3 elements, namely spatial planning and preparation of the medicine warehouse, safeguarding the quality of medicines, and recording medicine stock. Medication storage errors can cause drug shortages, losses due to lost or damaged and expired drugs, and also result in the potency of a drug decreasing which then results in it being ineffective if consumed by the patient. The aim of this research is to determine the suitability of drug storage and determine the efficiency of drug storage at the Sleman Health Center, Yogyakarta City and Bantul. This research is non-experimental research, with a descriptive qualitative research type and design. The results of research on drug storage in the three community health centers meet the standards in the